PENERAPAN PENDEKATAN ILMIAH DENGAN STRATEGI EVERYONE IS A TEACHER HERE DALAM PEMBELAJARAN MATEMATIKA DI SMPN 3 PUJON SATU ATAP - Kusumawardani, Puspa Ristina (Study Program of Mathematics Education University of Muhammadiyah Malang, 2017)
This research is the application of research that aims to: 1), describes theapplication of a scientific approach to learning strategy everyone is a teacher here 2) describe the motivation of students in the scientific approach to learning strategy everyone is a teacher here, and 3) describe the communication capabilities student in writing at a scientific approach to learning strategy everyone is a teacher here. The approach used in this study is a qualitative and quantitative approach is descriptive. This research was conducted in SMP Negeri 3 Pujon Satu Atap on 22 April-25 April 2015. The object of this research is the activity or process of student mathematics communications in writing and student motivation through a scientific approach to learning strategy everyone is a teacher here. Subject in this study were students of class VIII-B SMP Negeri 3 Pujon Satu Atap. Instruments used in this research is observation sheets, test sheets and sheets questionnaire. The procedure of this study were: 1) the planning stage 2) the stage of implementation and 3) the final stage. The results showed that: (1) There is an increase in student motivation after the adoption of a scientific approach to learning strategy everyone is a teacher here. (2) In the article there is an increasing communications capabilities results indicate that mathematical communication skills in writing the second test is better than the first test.